Impact of Prosthesis-Patient Mismatch on Survival after Mitral Valve Replacement: A Meta-analysis - Hwang, Ho-Young; Sohn, Suk-Ho; Jang, Myoung-jin (The Thoracic and Cardiovascular Surgeon, 2019)
Background Numerous studies have demonstrated a negative impact of prosthesis-patient mismatch (PPM) on long-term clinical outcomes after aortic valve replacement. However, the impact of PPM after mitral valve replacement (MVR) on clinical outcomes is still controversial. This study was conducted to evaluate the impact of PPM on early and long-term survival after MVR.Methods A literature search of five databases was performed. The primary and secondary outcomes were all-cause mortality and early mortality, respectively. Subgroup analyses were performed according to the risk of bias, patients' age, proportion of female patients, and proportion of patients with mechanical MVR.Results Eleven nonrandomized studies including 8,072 patients were included in this meta-analysis. The overall incidence of PPM was 58.0% (range: 10.4–85.9%). The odds ratio of early mortality in nine studies was not significantly different between the PPM and non-PPM patients (odds ratio: 1.35; 95% confidence interval [CI]: 0.98–1.86). A pooled analysis in 11 studies demonstrated that all-cause mortality after MVR was higher in the PPM than non-PPM patients (hazard ratio [HR]: 1.39; 95% CI: 1.09–1.77). This analysis revealed a moderate to high heterogeneity (I2 = 69.4%). When pooled analyses were performed in two subgroups according to the proportion of patients with mechanical MVR, there were low heterogeneity in each group. No other subgroup analyses demonstrated a significant difference in the HR of all-cause mortality. Funnel plots and Egger's tests showed no visually and statistically significant publication bias.Conclusion The present meta-analysis indicates that PPM negatively affects long-term survival after MVR.
Keywords: mitral valve; surgery; heart valve; outcomes; mortality